EDUKASI DAN INOVASI PEMBUATAN MIE BAYAM SEBAGAI ALTERNATIF KONSUMSI PANGAN SEHAT BAGI MASYARAKAT - Widijanto, Hery; Calista, Cinta Renaya; Nafissa, Anathaya; Pratama, Whilyan; Rohmala, Rengganis Murtya (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2025)
The increasing consumption of instant food containing excessive food additives has raised significant health concerns among households in Indonesia, including those in Gambiranom Village, Wonogiri District. This community service program was designed to offer a healthier and locally sourced alternative, namely spinach-based fresh noodles, through a structured combination of education, demonstration, and participatory practice. The program was implemented in July 2025 using a participatory descriptive method consisting of field surveys, risk-based socialization on food additives, hands-on demonstrations of spinach noodle preparation, and collaborative practice sessions involving ILP cadres. Qualitative observations were used to analyze changes in knowledge, participation, skills, and early behavioral shifts. The results show strong enthusiasm and high engagement throughout the activity. Participants demonstrated improved understanding of food additive risks, better decision-making in household food choices, and increased confidence in replicating spinach noodle production independently at home. Early indications also suggest interest in developing spinach noodles as a micro-enterprise product, supported by the availability of local agricultural commodities and growing consumer demand for healthy food options. Spinach noodles offer nutritional benefits including natural colorants and essential vitamins making them a valuable alternative to conventional instant noodles. For sustainability, the program recommends advanced mentoring, entrepreneurship training, product development guidance, and support for community-based marketing initiatives. Overall, the integrated education demonstration participation approach proved feasible and effective in reducing dependency on instant food products, strengthening household food literacy, and optimizing the use of locally available resources within rural communities for broader long-term benefits.